Control Problems of Discrete-Time Dynamical Systems - Hasegawa, Yasumichi (Lecture Notes in Control and Information Sciences, 2013)
This monograph deals with control problems of discrete-time dynamical systems which include linear and nonlinear input/output relations. It will be of popular interest to researchers, engineers and graduate students who specialized in system theory. A new method which produces manipulated inputs is presented in the sense of state control and output control. This monograph provides new results and their extensions which can also be more applicable for nonlinear dynamical systems. To present the effectiveness of the method, many numerical examples of control problems are  provided as well.